The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1128/aac.00590-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Porins in the Susceptibility of Mycobacterium smegmatis and Mycobacterium chelonae to Aldehyde-Based Disinfectants and Drugs

Abstract: Nosocomial outbreaks attributable to glutaraldehyde-resistant, rapidly growing mycobacteria are increasing. Here, evidence is provided that defects in porin expression dramatically increase the resistance of Mycobacterium smegmatis and Mycobacterium chelonae to glutaraldehyde and another aldehyde disinfectant, ortho-phthalaldehyde. Since defects in porin activity also dramatically increased the resistance of M. chelonae to drugs, there is thus some concern that the widespread use of glutaraldehyde and ortho-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 33 publications
(29 reference statements)
1
51
2
Order By: Relevance
“…Resistance of Acanthamoeba trophozoites to glutaraldehyde raises important questions about the potential association of glutaraldehyde-resistant Acanthamoeba with nontuberculous mycobacteria (NTM) that can also resist glutaraldehyde and grow within amoebae (18,23,58). It has been demonstrated that the resistance of NTM to glutaraldehyde is at least partially due to mutations in cell wall porins and that these mutations also increase the resistance of NTM to antibiotics commonly used to treat these infections (53). Furthermore, mutations in the same genes also increase the intra-amoebal survival capacity of NTM (49).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of Acanthamoeba trophozoites to glutaraldehyde raises important questions about the potential association of glutaraldehyde-resistant Acanthamoeba with nontuberculous mycobacteria (NTM) that can also resist glutaraldehyde and grow within amoebae (18,23,58). It has been demonstrated that the resistance of NTM to glutaraldehyde is at least partially due to mutations in cell wall porins and that these mutations also increase the resistance of NTM to antibiotics commonly used to treat these infections (53). Furthermore, mutations in the same genes also increase the intra-amoebal survival capacity of NTM (49).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that atypical mycobacteria such as M. chelonae and M. smegmatis are showing increased resistance to these chemicals due to defects in porin expression in the bacterial cell walls [14]. Porins are cell wall proteins found in Mycobacteria and have been known to create channels that allow the passage of small hydrophilic molecules, such as antibiotic drugs, through the highly hydrophobic mycobacterial cell wall [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although 2% GTA resistance is considered a rare event in mycobacteria, RGM strains with low susceptibility to GTA have already been described, most of them related to M. chelonae species [17][18][19] . Nomura et al 18 submitted 4 randomly selected M. chelonae isolates recovered from bronchoscope washing machines to GTA suspension tests.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated viable and reproducible mycobacterial cells even after 60-min exposure to this biocide. Svetlíkova et al 19 have proposed that defects of mycobacterial porins may be possibly represent the main mechanisms involved in resistance to aldehyde-based disinfectants.…”
Section: Discussionmentioning
confidence: 99%